Pengaruh Pemberitaan Aksi Premanisme terhadap Tingkat Kecemasan Pedagang dan Pengunjung GOR Panatayudha, Kabupaten Karawang - Shiyam Ramli; Zainal Abidin; Eka Yusup (Neolectura, 2022)
The role of online mass media is very influential in providing information about news of acts of thuggery crimes, so that someone knows and obtains information that is happening on the phenomenon of thuggery crimes that have recently disturbed traders and visitors. This study aims to determine the effect of mass media coverage on the level of anxiety of traders and visitors to Panatayudha Sports Center. The method in this research is descriptive and verification method. This type of research is quantitative research. The population in this study included 100 traders and visitors to Panatayudha Sports Center. The analytical tool used in this research is simple linear regression analysis. The results showed that News of Thugs Action had an effect on the level of anxiety of traders and visitors at Panatayudha Sports Center, Karawang Regency.